Anoka Ramsey Community College, Exploring America's Communities. Progress Report - Anoka Ramsey Community Coll., Coon Rapids, MN.; Anoka Ramsey Community Coll., Coon Rapids, MN. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
In 1996, Minnesota's Anoka Ramsey Community College (ARCC) participated in the Exploring America's Communities project sponsored by the American Association of Community Colleges. The project works to strengthen the teaching and learning of American History, literature, and culture at U.S. community colleges. The grant application from the ARCC team specified three areas for action: inclusion of concepts of pluralism and identity into teaching and activities, development of an interdisciplinary course, and organizing a series of Internet-based conversations for ethnically diverse student bodies. The major accomplishments to date can be divided into two categories: communicating the program's efforts to the college community and hosting events. Bringing faculty into the project was accomplished by one-on-one meetings, and a newsletter maintaining the presence of the subject for faculty and administrators was started. A week-long screening of the video "Exploring America's Communities Teleconference" was presented. Following the film, discussions on the subjects of community and identity were held. Additionally, a pair of workshops were held to discuss curriculum changes. Future projects under development include an Internet link-up, which will enlarge student-to-student communication. Faculty are also making substantial progress in curriculum transformation, and team members will continue to supply them with resources and encouragement. (HAA)
Sponsoring Agency: National Endowment for the Humanities (NFAH), Washington, DC.
Sponsoring Agency: American Association of Community Colleges, Washington, DC.
ERIC Note: In: National Conference on American Pluralism and Identity Program Book (New Orleans, LA, January 18-19, 1997); see JC 970 087.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Studies; Community Colleges; Computer Mediated Communication; Cultural Pluralism; Culture; Curriculum Development; History Instruction; Instructional Improvement; Interdisciplinary Approach; Literature; Program Descriptions; Two Year Colleges; United States History; United States Literature; Workshops; Anoka Ramsey Community College MN; Reports, Descriptive